AVALIAÇÃO DE DESEMPENHO ZOOTÉCNICO DO PIAU CORRÓ (Leporinus lacustris) SOB DIFERENTES DENSIDADES DE ESTOCAGEM - SILVA, Maria Eduarda Vasconcelos Mendes1 (maendeszoo56@gmail.com),; LEÃO, Fernanda Couto,; ACUNHA, Rubia Mara Gomes,; ALMEIDA, Rômulo Guilherme,; COSTA, Deliane Cristina,; CAMPOS, Cristiane Meldau de, (ANAIS DO ENIC, 2023)
-